Upaya Guru Akidah Akhlak dalam Pembinaan Akhlak Siswa di MTs Al-Fathimiyah Karawang - Inez Auliana Nariswari; Tajuddin Nur; Yayat Herdiana (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
Morals are the main foundation in the formation of a complete human person. In human life, morality occupies an important place, as individuals, communities and nations. In the family environment, parents have a very important role in personality development and forming morals, especially for children, in the social environment the community also has a role in personality development and moral formation, then in the school environment, teachers have the task of fostering and shaping student morals. The purpose of the researcher conducting the research was to find out the efforts of the moral aqidah teachers in fostering students' morals. The research method used is a qualitative method with data collection techniques through observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results showed that the morals of students at MTs Al-Fathimiyah Karawang are different and varied because each individual has an innate character and the influence of the environment around them, the efforts that have been made by teachers of moral aqidah in fostering students' morals are through: exemplary students always draw closer to Allah SWT. The method used is the method of giving advice, habituation, example, which aims to increase students' faith, respect fellow human beings, and obey teacher orders and school rules.